Innovation Aversion in Financial Advising: Ambiguity ‎Resolution of Stock Market Investors - K, Umamaheswari; A V V S, Dr. Subbalakshmi (International Journal of Basic and Applied Sciences, 2025)
Robo-advisors have integrated into financial advisory services, providing consumers with ‎regular investment guidance. Yet, it remains unclear how their visual design affects decision-making in high-risk and uncertain situations, like taking investment advice. This study focuses ‎on preferences and willingness to adopt Robo-Advisors in stock market investments. And, ‎investigated whether the Robo-Advisors are suitable for small investors or investors with less ‎experience in the Stock market. This study investigates the phenomenon of innovation aversion in ‎financial advising, focusing on how stock market investors respond to ambiguity and ‎uncertainty associated with emerging advisory technologies. Through a mixed-method ‎approach combining surveys and in-depth interviews with individual investors, the study ‎reveals that while technological innovation offers potential benefits in terms of efficiency and ‎cost-effectiveness, perceived complexity and lack of personal interaction contribute ‎significantly to innovation aversion. Inferential statistics like one-way ANOVA, Chi-Square ‎, and Regression were used to analyse the adoption and satisfaction of using Robo-Advisors ‎from the data of 119 respondents among residing and Non-residing Indians with the help of ‎IBM SPSS. Thematic analysis was used on qualitative data. The study reveals that the Non-resident Indians have greater satisfaction with these Robo-advisors’ platforms. Beginner ‎investors prefer Robo-advisors for their straightforwardness, while experienced investors tend ‎to be more cautious. Both groups, however, exhibit limited awareness of Robo-advisors, ‎despite the potential benefits they present‎.